Video documental “Memorias y relatos políticos de los jubilados de la Plaza Grande”. - Sandoval Vega, Odalis Natasha (2016)
The product in question is an ethnographic synthesis of the social memory of the retired people that spend their days in "Plaza Grande" from Quito. Who, taking into account their own experiences and stories, recount the facts and people who left their mark on Ecuador's political history during the 80's and 90's. Starting from compilation of such testimonials with depth interviews, a new alternate history of the country is developed, in which the narrators are all those anonymous people who lived all the social, political and economic impacts that occurred on those decades of democracy. The place where these stories were developed was symbolically consecrated as an essentially political place in the public understanding; therefore, a chronology of the progressive transformations of the Plaza Grande since its formation is the point that begins the story in progress. The outcome is an historical documentary product, whose legitimacy has academic and social relevance to establish itself as an alternative historiographical study of Ecuadorean politics, coming from the voices of citizens.